Analysis of the gut microbiome in sled dogs reveals glucosamine- and activity-related effects on gut microbial composition - Wang, Dong; Russel, William A.; Macdonald, Kaitlyn M.; De Leon, Valerie M.; Ay, Ahmet; Belanger, Kenneth D. (Frontiers in Veterinary Science, 2024)
The composition of the microbiome influences many aspects of physiology and health, and can be altered by environmental factors, including diet and activity. Glucosamine is a dietary supplement often administered to address arthritic symptoms in humans, dogs, and other mammals. To investigate how gut microbial composition varies with glucosamine supplementation, we performed 16S rRNA sequence analysis of fecal samples from 24 Alaskan and Inuit huskies and used mixed effects models to investigate associations with activity, age, and additional factors. Glucosamine ingestion, age, activity, sex and diet were correlated with differences in alpha-diversity, with diversity increasing with age and decreasing in dogs consuming glucosamine. Beta-diversity analysis revealed clustering of dogs based on glucosamine supplementation status. Glucosamine supplementation and exercise-related activity were associated with greater inter-individual pairwise distances. At the family level, Lactobacillaceae and Anaerovoracaceae relative abundances were lower in supplemented dogs when activity was accounted for. At the genus level, Eubacterium [brachy], Sellimonus, Parvibacter, and an unclassified genus belonging to the same family as Parvibacter (Eggerthellaceae) all were lower in supplemented dogs, but only significantly so post-activity.Our findings suggest that glucosamine supplementation alters microbiome composition in sled dogs, particularly in the context of exercise-related activity.